Do travel images affect international students’ on-site academic value? New evidence from the Malaysia’s ‘higher edutourism’ destination - Lam, Jason MS; Ariffin, Ahmad Azmi M (Journal of vacation marketing, 2019)
While previous studies have merely focused on travel destination image (TDI) with respect to influencing international students’ decision-making for academic destinations (i.e. the pre-experience stage), research on TDI relating to students’ on-site educational experiences and future behavioural intentions remain scant. This study introduces the ‘higher edutourism’ concept as a key enabler from the higher education market in attracting international students for the tourism industry. This study attempts to extend the TDI paradigm by empirically examining cognitive, affective and conative TDIs from a multidimensional perspective and its effects on overall perceived value, while also testing the indirect effects of TDIs. A total of 515 questionnaires were analysed using structural equation modelling. The results confirmed that cognitive TDI would positively impact affective TDI, perceived value and subsequently, conative TDI. Theoretical and practical implications for policymakers, higher education administrators and tourism marketers are also discussed.